Inclusion and Exclusion: Dalit and Marginalized Participation in Local Government Planning in Nepal - Adhikari, Govinda (Historical Journal, 2025)
This study examines the participation of Dalits and marginalized communities in local government planning and budgeting within Nepal’s federal government framework. It explores the constitutional and legal frameworks, especially the Local Government Operational Act (LGOA) and the Constitution of Nepal, which support inclusion. Through literature reviews, Focus Group Discussions (FGDs), and Key Informant Interviews (KIIs) conducted in three municipalities in Koshi Province, the research evaluates both the provisions and their grassroots implementation. The key finding of the study is that while legal provisions for the participation of Dalits and marginalized communities in local government planning and budgeting exist, their actual implementation at the grassroots level is limited, with significant gaps in consultation, awareness, and capacity. The findings underscore the need for clearer mandatory provisions, consultation mechanisms, capacity-building, and monitoring frameworks to enhance inclusive governance. The study concludes with recommendations for targeted interventions to improve the practice of participatory planning and budgeting. These results have important implications for improving participatory governance, enhancing local government planning, and ensuring meaningful inclusion of marginalized groups.